Holy Earth: Harnessing Religious Ethics and Faith-Based Action to Combat Climate Change - Sugiant, Reza Nurdiana; Shahruddin, Mohd Solahuddin (FISIP UIN SGD Bandung, 2025)
This study explores the role of religion in addressing climate change by examining religious teachings on environmental stewardship, the involvement of faith-based communities in climate mitigation efforts, and the broader social impact of religious perspectives on environmental issues. Employing a literature review approach with content analysis, this research systematically analyzes academic literature, religious texts, and environmental reports to uncover the ecological principles embedded within Islam, Christianity, Hinduism, and Buddhism. The findings indicate that religious teachings provide a strong ethical foundation for environmental responsibility, while faith-based organizations actively engage in sustainability initiatives, including reforestation campaigns, carbon emission reduction programs, and ecological awareness education. The study concludes that religion plays a crucial role in fostering moral and spiritual motivation for environmental action. Consequently, fostering collaboration among religious leaders, policymakers, and scholars is essential to strengthening the integration of religious values into global climate change strategies for a more sustainable and equitable future. Contribution: This study highlights the synergistic potential between religious frameworks and climate action, demonstrating how spiritual values ​​can drive real environmental solutions. By analyzing doctrinal principles and grassroots efforts across major religions, the study provides a roadmap for integrating ethical imperatives into sustainability strategies.